TNF-α -308 G/A Gene Polymorphism as a Risk Factor for Pulmonary Tuberculosis in Cirebon, Indonesia - Oktaviyati, Nurfithria; Pratamawati, Tiar Masykuroh; Nauphar, Donny (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2025)
Background: Mycobacterium tuberculosis, the causative agent of pulmonary tuberculosis, spreads via droplets. The TNF-α-308 G/A gene polymorphism is one of the host genetic variables that may affect an individual's vulnerability to the disease. However, this polymorphism has not been studied in Cirebon. Aims: To analyze the TNF-α -308 G/A gene polymorphism as a risk factor for the occurrence of pulmonary tuberculosis in Cirebon. Methods: A total of 64 participants joined part in an analytical observational study using a case-control design at the Biomolecular and Genetics Laboratory, Faculty of Medicine, Universitas Swadaya Gunung Jati, Indonesia. DNA extraction from blood samples, ARMS-PCR genotyping, and 1.5% electrophoresis gel visualization were all part of the data gathering process. The chi-square test was used to analyze the data. This study including inclusion criteria, exclusion criteria, and sample control for the research. Results: According to the study, there is no link between Cirebon's risk of pulmonary tuberculosis and the polymorphism in the TNF-α-308 G/A gene (OR = 0.462; P > 0.05). However, the study shown a protective factors which means that individuals with the TNF-α -308 G/A gene polymorphism have a lower risk of developing pulmonary tuberculosis compared to those without the polymorphism. Conclusion: The TNF-α-308 G/A gene variant is not associated with an increased risk of pulmonary tuberculosis in the Cirebon community.